PENGARUH ASSET INSTRUMEN KEUANGAN DAN FREE CASH FLOW TERHADAP NILAI PERUSAHAAN - Septanta, Rananda; Latif, Adi Sofyana; Arslan, Rijal (Jurnal Manajemen dan Bisnis, 2022)
This study entitled The Effect of Financial Instrument Asset and Free Cash Flow on Firm Value. The purpose of this study was to determine whether financial instrument assets and free cash flow have an effect on firm value. This research is a descriptive quantitative study, using statistical tests and literary methods. The research companies listed on the Indonesia Stock Exchange in 2017-2021. The sample was selected using purposive sampling method and obtained 19 companies that became the sample. The type of data used is secondary data, in the form of company annual reports. Data analysis used descriptive statistics, classic assumption test, coefficient of determination and multiple linear regression analysis. Data processing uses the SPSS program to perform multiple linear regression analysis, coefficient of determination, normality test, multicollinearity test, autocorrelation test and hypothesis testing. The results of this study indicate that financial instrument assets have no effect on firm value, free cash flow has a significant effect on firm value.